P-P55 CT-PET use in potentially resectable pancreatic cancer. (16th December 2021) - Thorne, Thomas; McKay, Siobhan C; Hall, Lewis; Wilkin, Richard; Pathak, Samir; Barrie, Jenifer; Moir, John; Roberts, Keith J
Abstract: Background: CT-PET has become increasingly used in the diagnostic pathway for pancreatic cancer (PC)and was introduced into National Guidelines (NICE) in 2018 in the United Kingdom. It can improve the diagnosis of metastatic disease, though some believe it is not significantly better than a staging CT and MRI, and there are concerns that it can significantly delay the treatment pathway for patients, without adding benefit. Methods: A retrospective national study undertaken by 26/27 specialist pancreatic resectional centres in the United Kingdom. All adult patients listed for pancreatoduodenectomy for suspected PC were included. Baseline demographics, length of pathway (days from MDT to surgery), number and type of investigations, interventions (ERCP or PTC) and associated complications were recorded, in addition to the operation performed and 12-month survival. Patients undergoing neoadjuvant chemotherapy were excluded. Results: 1709 cases were entered from 2017-2020. 155 patients were excluded due to neoadjuvant chemotherapy, with 8 further patients excluded due to incomplete data entry. The median age was comparable for patients undergoing CT-PET (68 years IQR 60.0-73.0) and those who did not undergo CT PET (68 years IQR 60.0-74.0). 363/1546 patients (23.5%) underwent a pre-operative CT-PET. There was a significantly longer pathway with CT-PET (56 vs 42 days, p < 0.001) and a non-significant tendency towards an increased bypass rate with CT-PET (9.9% vs. 7.8%, p = 0.065), and no improvement in survival (1-year survival 76.9% vs 75.7%, p = 0.712). Conclusions: There is a statistically significant increase in the length of pathway with CT-PET, without any improvement in bypass rate or one year survival compared the no-CT-PET group. CT-PET undoubtedly has benefits but should be used selectively rather as standard investigation for all patients as failed to demonstrate survival improvement.